Predictive Factors of Tuberculosis Preventing Behaviors among Muslim Elderlies Living in Coastal Community, Tha Sala District, Nakhon Si Thammarat Province - Aubdulla, Ornruethai; Kaewsawat, Supreecha (Princess of Naradhiwas University Journal, 2021)
This research was a cross-sectional analytical research aimed to study factors predicting the TB preventive behaviors among Muslim elders. The sample participating in this study was 384 elderly Muslims living in the coastal community of Tha Sala district, Nakhon Si Thammarat province, and they were randomly selected by simple random sampling. Data collection was done during July to August 2019 with interviewed questionnaires on perceived severity and susceptibility of the disease and TB preventive behaviors. The questionnaires had passed the content validation test by 3 experts with the consistency between .67 – 1, and the alpha Cronbach coefficient equals to .833, .815, .907, respectively. Data was analyzed by frequency, percentage and multiple regression with enter regression method. The results showed that age (X2) (p<.001, β = .210), education (X4) (p = .006, β = .135) and single-family characteristics (X7) (p = .009, β = -.123) were able to predict tuberculosis (TB) prevention behaviors among Muslim elders with statistically significant. Regarding the threat perception consisting of perceived susceptibility and severity were found that only the perceived severity (X9) (p < .001, β = .279) was able to predict TB prevention behaviors among Muslim elders with statistically significant (R2 = .177). This research suggested that public health staffs should be more campaigns and promotion relating to TB prevention behaviors among Muslim elders by creating a channel to perceive the severity of the disease through news channels with public relations to raise awareness of the disease prevention